Literature Review of the Benefits of Lean Manufacturing on Industrial Performance and Proposed Applications in the Defense Industries - Johan, Andi; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
Lean manufacturing is a production practice that considers all existing resource expenditures to get economic value to customers without any waste. Lean Manufacturing has been widely implemented in various industries to improve performance and competitiveness. The purpose of this article is to explore the benefits of implementing Lean Manufacturing in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 35 international journal articles published from 2010 to 2021 regarding the application of the six sigma method in various industrial sectors and the defense industry. The analysis used used 25 content analyzes of journal articles, which had been collected and then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of the Lean Manufacturing concept is a strategy for companies to obtain various benefits, including being able to increase production productivity, companies, increasing process efficiency in producing products, reducing production costs so that product selling prices can be lower, increasing product competitiveness from companies so that the Lean Manufacturing method is recommended to be applied in the defense industry.